Effect of gabapentin pretreatment on myoclonus after etomidate: a randomized, double-blind, placebo-controlled study - Yılmaz Çakirgöz,Mensure (2016)
Abstract Aim: To evaluate the effects of three different doses of gabapentin pretreatment on the incidence and severity of myoclonic movements linked to etomidate injection. Method: One hundered patients, between 18 and 60 years of age and risk category American Society of Anesthesiologists I-II, with planned elective surgery under general anesthetic were included in the study. The patients were randomly divided into four groups and 2 h before the operation were given oral capsules of placebo (Group P, n = 25), 400 mg gabapentin (Group G400, n = 25), 800 mg gabapentin (Group G800, n = 25) or 1200 mg gabapentin (Group G1200, n = 25). Side effects before the operation were recorded. After preoxygenation for anesthesia induction 0.3 mg kg−1 etomidate was administered for 10 s. A single anesthetist with no knowledge of the study medication evaluated sedation and myoclonic movements on a scale between 0 and 3. Two minutes after induction, 2 µg kg−1 fentanyl and 0.8 mg kg−1 rocuronium were administered for tracheal intubation. Results: Demographic data were similar. Incidence and severity of myoclonus in Group G1200 and Group G800 were significantly lower than in Group P; sedation incidence and level were appreciably higher compared to Group P and Group G400. While there was no difference in the incidence of myoclonus between Group P and Group G400, the severity of myoclonus in Group G400 was lower than in the placebo group. In the two-hour period before induction other than sedation none of the side effects related to gabapentin were observed in any patient. Conclusion: Pretreatment with 800 mg and 1200 mg gabapentin 2 h before the operation increased the level of sedation and reduced the incidence and severity of myoclonic movements due to etomidate.